2014
DOI: 10.2298/vsp1411006a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of conventional and digital radiography capacities for distinguishing dental materials on radiograms depending on the present radiopacifying agent

Abstract: The materials which incorporate CHI3 OR BaSO4 as radiopacifying agents are expected to be significantly more radiopaque on a digital sensor than on film. During clinical practice one should concern to the quality of contrast assessment obtained by digital according to conventional radiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 25 publications
0
23
1
5
Order By: Relevance
“…The discrepancies in radiopacity among the tested composite materials are mainly attributed to differences in filler composition, and more specifically in concentration and type of included radiopacifying agents . As it mentioned previously, the radiopacifying agents of the dental composite restoratives are inorganic compounds with high atomic numbers, which are incorporated as fillers.…”
Section: Discussionmentioning
confidence: 94%
“…The discrepancies in radiopacity among the tested composite materials are mainly attributed to differences in filler composition, and more specifically in concentration and type of included radiopacifying agents . As it mentioned previously, the radiopacifying agents of the dental composite restoratives are inorganic compounds with high atomic numbers, which are incorporated as fillers.…”
Section: Discussionmentioning
confidence: 94%
“…Mineral trioxide aggregate is expensive, and accordingly, Portland cement is currently being considered as an alternative root-filling material which could be mixed with a suitable radiopacifier by the clinician [4,[5][6][7]. In this respect, the findings of this study indicate that barium sulphate and zirconium oxide are superior to bismuth oxide with respect to setting time.…”
Section: In Vitro Bioactivitymentioning
confidence: 91%
“…Recent studies have indicated that a number of candidate radiopacifiers, including barium sulphate and zirconium oxide, may possess superior physicochemical, mechanical or biological properties to those of bismuth oxide [3][4][5][6][7][8]. Mineral trioxide aggregate is expensive, and accordingly, Portland cement is currently being considered as an alternative root-filling material which could be mixed with a suitable radiopacifier by the clinician [4,[5][6][7].…”
Section: In Vitro Bioactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Micromechanical properties were not affected by using different liquid components [64]. When adding different radiopacifiers to CS cements, engineers should be careful having in mind that some radiopaque agents (BaSO4 and CHI3) result in different radiopacities of the final mixture on dental film and digital sensor [65]. The variations in the radiopacity of tested cements on film and CCD-based digital sensor arise from the different sensitivity of the detector used.…”
Section: Physico-chemical Properties Of Cs Cementsmentioning
confidence: 99%